Level of Community Participation in Development of Denai Lama Village Tourism Village - Silalahi, Nelly Hermin Elisabeth; Dalimunthe, Femmy Indriani; Kesuma, Sinar Indra (Jurnal Ilmiah Global Education, 2024)
This research delves into the community participation in developing a tourism village in Denai Lama Village, Pantai Labu District. Employing quantitative methods and factor analysis on 85 samples, which includes pokdarwis officials and traders from Pasar Kamu and Paloh Naga, the study drew significant findings. The results indicate that manipulation, therapy, information, placement, collaboration, and citizen control significantly influence community participation. However, consultation and delegation factors showed lesser impact. There are both supporting and constraining elements affecting community involvement. Key enablers for active community participation include available opportunities, individual willingness, and capability to effectively engage. On the other hand, individual attributes and demographics, such as age, gender, and education level, can inhibit participation. The study highlights the vital role of government and institutional intervention in promoting community engagement in decision-making processes and in the execution of tourism village projects. For the Denai Lama Village, it's crucial to understand how human demographics may limit community involvement, guiding strategies to enhance active participation in future tourism village developments.